“Nizhegorodskaya” (Ryazanskaya) transport hub in Moscow - Bashkaev, Timur (project baikal, 2021)
The article features the architectural solution and purpose of the Nizhegorodskaya transport and interchange hub, as well as the importance of interaction between the leading design teams of different profiles. It describes the symbolic and artistic component of the project and its implementation.
Keywords: transport hub; Moscow; navigation; passenger flows; architecture; art-object